2006
DOI: 10.1016/j.vaccine.2005.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and protective efficacy in monkeys of purified inactivated Vero-cell SARS vaccine

Abstract: The purified inactivated SARS vaccine could induce high levels of neutralizing antibody, and protect the monkeys from the challenge of SARS-CoV. The SARS vaccine prepared in the study appeared to be safe in monkeys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
75
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 13 publications
4
75
0
1
Order By: Relevance
“…As first generation of SARS vaccines, the inactivated SARS-CoV vaccine has been tested in preclinical and clinical studies, and shown its capacity to elicit sterilizing immunity in several animal models [13][14][15][16][17][18]. Our results here indicate that although the major neutralizing domain of SARS-CoV is functional in the inactivated vaccine preparation, some important neutralizing epitopes (e.g.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…As first generation of SARS vaccines, the inactivated SARS-CoV vaccine has been tested in preclinical and clinical studies, and shown its capacity to elicit sterilizing immunity in several animal models [13][14][15][16][17][18]. Our results here indicate that although the major neutralizing domain of SARS-CoV is functional in the inactivated vaccine preparation, some important neutralizing epitopes (e.g.…”
Section: Discussionmentioning
confidence: 68%
“…Several inactivated SARS vaccines prepared by conventional protocols, e.g. beta-propiolactone, formaldehyde or UV light, have been tested in preclinical studies [13][14][15][16][17][18][19]. These killed whole virus vaccines are effective in terms of their capac-0264-410X/$ -see front matter…”
mentioning
confidence: 99%
“…Inactivated whole-virus preparations of SARS-CoV have been shown to induce protective immunity in small-animal models (2)(3)(4)(5) and primates (6,7). However, large-scale growth of a highly pathogenic agent introduces the risk of laboratory infection, which indeed has occurred (8).…”
mentioning
confidence: 99%
“…An additional limitation of previous studies of vectored and inactivated SARS-CoV vaccines in non-human primates, the model that is most similar to humans, is that protective efficacy was measured by quantitation of challenge SARS-CoV shed in respiratory secretions (6,7,16,20). It is now known that the virus replication in nasal and lung tissues occurs at a much higher level than previously appreciated and is poorly represented by shed virus (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation